Letter from Max Bredig to Federico and Annemarie Schnell, December 15, 1942 - Bredig, Max Albert (1942)
Max Albert Bredig (1902-1977) writes to Fritz (Federico) and Annemarie Schnell. Bredig updates Federico about a letter he received from Alfred (1900-1944) and Eva Schnell (1913-1944), his job, his personal life, and his family.
Keywords: Bredig, Max Albert, 1902-1977; Schnell, Eva, 1913-1944; Schnell, Alfred, 1900-1944; Schnell, Federico; Homburger, Marianne, 1903-1986; Chemists